Peran Entrepreneur Orientation Terhadap Volatilitas UKM Dengan Budaya Lokal Sebagai Pemediasi - Syahril Djaddang; Shanti Lysandra; Mulyadi (JRB-Jurnal Riset Bisnis, 2018)
This research aim is to find growth strategy of small and medium enterprises (SME) oriented with entrepreneurship by looking at enterpises’ growth and sales based on the ethical discernment of the local culture of SME. This research is conducted in 5 areas i.e. Jakarta, Bogor, Depok, Tangerang and Bekasi. This research is also meant to analyze the impact of strategic growth as prediction tool of the volatility of SME (EO and its scope) and the potential effect of growth strategy on the volatility of SME. Developing literature model of small and medium enterprises’ volatility research with strategic growth based on the ethical discernment of the local cultures. Research method used is quatitative method with random sampling on the entire population of SME in Jabodetabek and tool of analyze used is Struktur Equation Modeling using WarpPLS 5.0 Program. Variance or component based Struktur Equation Modeling used to test hypotheses. The result of this research positively and significantly gives contribution to the role of the ethical discernment of the local cultures of SME and entrepreneurship orientation / strategic growth projected with innovative, risk taking and pro-active, in which give contribution of 56%, 80%, 83% respectively to the entrepreneurship orientation/strategic growth of SME against volatility of SME that is fully moderated by the ethical local culture of SME in Jabodetabek.